The long-term effects of hospitalization on health care expenditures: An empirical analysis for the young-old population - Irene Torrini; Claudio Lucifora; Antonio Russo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2022)
We investigate the short- and long-term effects of hospitalization on different types of health care expenditures (HCE). A dynamic DID model with variation in treatment timing is specied and estimated using register data of individuals aged 50-70 residing in Milan, Italy, and observed over the period 2008-2017. We analyze on the entire population and carry out heterogeneous analysis by leading cause of hospitalization and presence of chronicity or disability. We find evidence of a large and persistent effect of hospitalization on total HCE, with future medical expenses mostly accounted for by inpatient care. Considering all health treatments, the overall effect is sizable, accounting for approximately twice the cost for any single hospital admission. We show that chronic and disabled individuals require greater post-discharge medical assistance especially for inpatient care and that cardiovascular and oncological diseases account together for more than half of expenditures on future hospitalizations. Alternative out-of-hospital management practices are discussed as a post-admission cost-containment measure.
Keywords: H51; I11; I18; 330; Health Care Expenditures; Hospitalization Effect; Health Shocks; Chronic Disease; Cardiovascular Disease; Cancer